(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses the study of aspectual semantics and proposes the theoretical foundations of this approach. The main content of the article is to show the difference between field theory and theory of semantic differences in the study of aspectuality. The composition of variation is determined, which makes up some significance of aspectual semantics in the field of predicate. During the analysis, it will be substantiated that semantics occurs on the basis of the causative meaning of the verb and the structural-semantic properties of the emotionally-causative units of the English and Uzbek languages are analyzed.